Lineage tracing reveals conversion of liver sinusoidal endothelial cells into hepatocytes. (10th August 2016) - Tan, Zhaoli; Chen, Keyan; Shao, Yong; Gao, Lihua; Wang, Yan; Xu, Jianming; Jin, Yang; Hu, Xianwen; Wang, Youliang
Abstract : Although liver sinusoidal endothelial cells (LSECs) have long been known to contribute to liver regeneration following injury, the exact role of these cells in liver regeneration remains poorly understood. In this work, we performed lineage tracing of LSECs in mice carrying Tie2‐Cre or VE‐cadherin‐Cre constructs to facilitate fate‐mapping of LSECs in liver regeneration. Some YFP‐positive LSECs were observed to convert into hepatocytes following a two‐thirds partial hepatectomy (PH). Furthermore, human umbilical vein endothelial cells (HUVECs) could be triggered to convert into cells that closely resembled hepatocytes when cultured with serum from mice that underwent an extended PH. These findings suggest that mature non‐hepatocyte LSECs play an essential role in mammalian liver regeneration by converting to hepatocytes. The conversion of LSECs to hepatocyte‐like (iHep) cells may provide a new approach to tissue engineering. Abstract : Our findings suggest that mature non‐hepatocyte LSECs play an essential role in mammalian liver regeneration by converting to hepatocytes. The conversion of LSECs to hepatocyte‐like (iHep) cells may provide a new approach to tissue engineering.